Advancing sustainable cattle farming as a climate strategy in Olancho, Honduras - Sandoval, Danny; Burkart, Stefan (2025)
Climate change presents a mounting threat to cattle systems in the department of Olancho, Honduras. With over 90% of producers reporting impacts from extreme climate events, particularly droughts, sustainable cattle practices have become a critical adaptive and mitigation strategy. This policy brief synthesizes the findings of a study conducted with 425 cattle producers across four municipalities, identifying levels of adoption of sustainable practices, access to climate information, and the relationship between these factors and climate vulnerability. Recommendations are made to improve institutional support, information systems, and financial incentives to expand adoption.